Utility and evaluation of applied project management processes within a large multicountry health systems development project conducted during the Coronavirus disease 2019 (COVID-19) pandemic - Kwon, Soo Young; Gautam, Sanjay; Poudel, Kritika; Banneheke, Hasini; Ferreira, Delfim; Gautam, Manish; Hau'ofa, Michelle; Mahmood, Nashmia; Phommalad, Bouahome; Sujan, Mohammad Julhas; Yangzom, Pema; Joh, Hea Sun; et al. (Clinical infectious diseases, 2023)
The increasing trends in antimicrobial resistance (AMR) continue to pose a significant threat to human health, with grave consequences in low- and middle-income countries. In collaboration with local governments and microbiology laboratories in South Asian and Southeast Asian countries, the Capturing Data on Antimicrobial Resistance Patterns and Trends in Use in Regions of Asia (CAPTURA) project worked to identify gaps and expand the volume of existing AMR data to inform decision-makers on how to best strengthen their national AMR surveillance capacity. This article describes overall project management processes and the strategies implemented to address the disruptive impact of the coronavirus disease 2019 (COVID-19) pandemic on the project activities across diverse contexts in different countries. Also, it assesses in-country team's feedback on the conduct of activities and their overall impact on project completion. The strategies employed were tailored to the specific context of each country and included increased communication and collaboration among consortium partners and in-country teams, as well as hiring of additional in-country team members. This paper highlights the importance of local representation and capacities as well as real-time (virtual) engagement with stakeholders, ensuring close monitoring of the local situation and ability to tailor context-specific mitigation strategies to continue project implementation during disruptive external circumstances.